Analysis of Consumption Data to Detect Commercial Losses Using Performance Evaluation Methods in a Smart Grid - Faria, Pedro; Vale, Zita; Souza, Andre [UNESP]; IEEE (Ieee, 2014)
Electric power networks, namely distribution networks, have been suffering several changes during the last years due to changes in the power systems operation, towards the implementation of smart grids. Several approaches to the operation of the resources have been introduced, as the case of demand response, making use of the new capabilities of the smart grids. In the initial levels of the smart grids implementation reduced amounts of data are generated, namely consumption data. The methodology proposed in the present paper makes use of demand response consumers' performance evaluation methods to determine the expected consumption for a given consumer. Then, potential commercial losses are identified using monthly historic consumption data. Real consumption data is used in the case study to demonstrate the application of the proposed method.
Keywords: Commercial losses; customer baseline load; performance evaluation methods; smart grid